Behcet's disease: clinical manifestations, current principles of diagnosis and therapy - T. A. Lisitsyna; Z. S. Alekberova; R. G. Goloeva; G. A. Davydova (Научно-практическая ревматология)
The lecture considers in detail modern ideas about the epidemiology, pathogenesis, and clinical manifestations of Behcet's disease/syndrome, as well as the principles of diagnosis, assessment of the activity and severity of the disease, and approaches to therapy.